2013
DOI: 10.4081/ijas.2013.e21
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance, Egg Quality and Biochemical Parameters of Three Way Crossbred Chickens with Reciprocal F1Crossbred Chickens in Sub-Tropical Environment

Abstract: A total of 225 hens (18 weeks of age) of each Rhode Island Red male x Fayoumi female (RIFI), Fayoumi male x Rhode Island Red female (FIRI) and White Leghorn male x FIRI female (RLH) were maintained on deep litter system for a period of 72 weeks of age. In floor pens, each crossbred chicken was randomly distributed between pens, with 21 to 24 birds of the same breed per pen (2.00 to 2.50 ft 2 /bird). The results revealed that the age of sexual maturity was lowest in RIFI followed by FIRI and RLH chickens. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…There is a clear association between the mice treatment with cadmium ( II) complex and the significant depletion of GPT activity at most doses in different tissues compared to cyclophosphamide could be attributed to the increased the permeability of the cell as well as the direct effect of the heavy metal on tissues [10]. Rikabi and Jawad [14] showed the damging effect of cadmium in the liver manifestested by an increase of AST,ALT and ALP, which specific marker of the liver cell damge . The decreased activities of GOT , GPT ,ACP and AIP indicate disturbance in the structure and integrity of cell organelles , like endoplasmic reticulum and membrane transport system , such damage to cell organelles has been reported in various studies [17] cadmium toxicity occurs through interactions with proteins that subsequently cause dysfunction of protein complex and organelles [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear association between the mice treatment with cadmium ( II) complex and the significant depletion of GPT activity at most doses in different tissues compared to cyclophosphamide could be attributed to the increased the permeability of the cell as well as the direct effect of the heavy metal on tissues [10]. Rikabi and Jawad [14] showed the damging effect of cadmium in the liver manifestested by an increase of AST,ALT and ALP, which specific marker of the liver cell damge . The decreased activities of GOT , GPT ,ACP and AIP indicate disturbance in the structure and integrity of cell organelles , like endoplasmic reticulum and membrane transport system , such damage to cell organelles has been reported in various studies [17] cadmium toxicity occurs through interactions with proteins that subsequently cause dysfunction of protein complex and organelles [18].…”
Section: Resultsmentioning
confidence: 99%
“…-Glatamate pyruvate transaminase (GPT) Kit L-Alanine 2-oxoglutarateaminotransferase was measured with 2,4 dinitrophenylhy-drazine according to method of Razzaq [13] -Alkaline phosphatase ( ALP) Kit was assessed using 4-aminoantipyrine according to method of R ikabi and Jawad [14].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported inter relationship between breed or strain of chicken and its effect on egg quality (Monira et al, 2003;Khawaja et al, 2013;Kabir et al, 2014) Korean native chicken (KNC), a domestic breed of Korea, have been studied to improve their production previously (Seo et al, 2013;Choi et al, 2015). However, published data on egg quality parameters and genetic effects of strains of Korean native chicken have barely been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Feed efficiency was calculated based on the method reported by Khawaja et al (2013). Further calculations were performed with the collected measurements data, to analyze the respective quality parameters.…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation